Predicting the tolerability of inhalation therapy as a stage of a personalized approach in the treatment of children with cystic fibrosis - K.V. Skriabinа; S.I. Ilchenko; A.O. Fialkovska (Zaslavsky O.Yu., 2023)
Background. Considering the features of basic therapy for chronic inflammatory bronchopulmonary process in cystic fibrosis (CF), which includes almost daily inhalation of pharmacological drugs (mucolytics, hypertonic saline (HS), antibiotics), evaluation of their tolerability is relevant in practice. The purpose of the study is to create a prognostic scale convenient for use in practical medicine, which would predict development of bronchial hyperreactivity syndrome in children with CF, based on clinical and anamnestic data, the results of molecular genetic research and inhalation tests with increasing concentrations of HS to prescribe personalized treatment. Materials and methods. The results of clinical and anamnestic, microbiological, biochemical, molecular and genetic studies and inhalation tests with increasing concentrations of HS were analyzed in 40 children with CF. The creation of the predictive algorithm was based on the application of correlation analysis, receiver operating characteristic analysis, binary logistic regression, Wald and Kullback method. Results. Two prognostic models have been created that can be used at different stages of providing medical care. Model 1 was built for the ambulatory stage of providing medical care to patients with CF, considering clinical and anamnestic data, molecular genetic predictors, as well as clinical symptoms during inhalation tests with increasing concentrations of HS. This model also can be used in young children who cannot perform spirometry to assess their external breathing function. For the highly specialized medical care, model 2 was created, which considers indicators of spirometric data of inhalation tests with increasing concentrations of HS and the level of exhaled nitric oxide. Conclusions. The developed models make it possible to calculate with high probability the risk of developing bronchial hyperreactivity to perform a personalized selection of HS and choose preventive brocholytic therapy as needed.